Artificial intelligence and the transformation of Arabic meaning: Challenges and opportunities - Oktari, Sri Jomila; Harahap, Desi Hariyanti; Hasaniyah, Nur (Abjadia : International Journal of Education, 2025)
This research discusses the use of artificial intelligence (AI) in Arabic language education and the transformation of Arabic meaning through AI. It also discusses the challenges and opportunities presented by AI in Arabic language education. Using the library research method, this study collects and analyzes various relevant literature sources to understand how AI can improve the Arabic language learning process. The results show that AI can improve the effectiveness of Arabic language learning by providing an interactive, diverse, and engaging platform, as well as providing quick and accurate responses to students. However, the research also found that there are some challenges presented by AI, such as the limited validity of information and the potential for cheating. The research also highlights the importance of accessibility of digital learning resources and interactive learning experiences that can motivate students in learning Arabic. Therefore, this study recommends that AI should be used effectively and responsibly in Arabic language education.